Hydrocracking catalyst and its preparation method and application

By modifying amorphous silicon-aluminum powder and metal ion loading technology, the pore structure and acidic distribution of hydrocracking catalysts are optimized, and the problems of diesel selectivity and freezing point of existing catalysts when treating Fischer-Tropsch wax oil are solved, achieving efficient and low-cost diesel preparation.

CN119746882APending Publication Date: 2025-04-04CHINA ENERGY GRP NINGXIA COAL IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411743187.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When treating Fischer-Tropsch wax oil, the diesel selectivity is low, the freezing point is high, the preparation process is complex, and the cost is high, making it difficult to take into account the needs of high diesel yield and low freezing point.

Method used

Modified amorphous silicon-aluminum powder is used as the catalyst support, and the pore structure and acidic position distribution are optimized through acid treatment and ammonium exchange, and the support is supported by group VIB metal ions and group VIII metal ions, which work together to improve catalytic activity and stability.

Benefits of technology

It improves the selectivity and quality of diesel fractions, reduces the freezing point of diesel, simplifies the preparation process, reduces production costs, and achieves efficient hydrocracking reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162950780000121
    Figure BDA0005162950780000121
  • Figure BDA0005162950780000122
    Figure BDA0005162950780000122
  • Figure BDA0005162950780000123
    Figure BDA0005162950780000123
Patent Text Reader

Abstract

The present invention provides a hydrocracking catalyst and a preparation method and application thereof. The preparation method comprises: acid-treating and ammonium-exchanging amorphous silicon-aluminum powder to obtain modified amorphous silicon-aluminum powder; mixing the powder with a binder and a sol to obtain a hydrocracking catalyst carrier; loading a first metal ion and a second metal ion thereon, drying and calcining to obtain a hydrocracking catalyst; the first metal ion is selected from the metal ions of the VIB group, and the second metal is selected from the metal ions of the VIII group. The present invention adopts amorphous silicon-aluminum powder with high pore volume and high specific surface area as the main active component of the hydrocracking catalyst carrier, and improves the pore size distribution and medium-strong acid content of the catalyst by acid modification and ion exchange, so that the catalyst has specific adsorption and diffusion properties, and has a specific effect on the preparation of diesel fraction materials using Fischer-Tropsch wax as raw material. The two metal ions work together to further improve its catalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy technology, and in particular to a hydrocracking catalyst and a preparation method and application thereof. Background Art

[0002] Fischer-Tropsch synthesis technology, as a process for converting synthesis gas (mainly composed of CO and H2) into long-chain hydrocarbons, has become one of the important means to cope with the increasing scarcity of global oil resources and increasing environmental pressure. The heavy distillate oil and heavy wax produced in the low-temperature Fischer-Tropsch synthesis process have a hydrocarbon structure dominated by normal alkanes, which is significantly different from traditional petroleum-based raw materials. These heavy products contain a high wax component and have a high freezing point, which limits their direct application as diesel. Therefore, hydrogenation and modification, especially cracking and isomerization, to increase the diesel yield of Fischer-Tropsch wax oil and reduce the freezing point of diesel have become key steps in refining high-value low-freezing point diesel.

[0003] Hydrocracking technology, with its wide adaptability of raw materials, flexible and diverse processing schemes, and excellent quality of finished oil, occupies an important position in the field of producing clean and efficient finished oil. In industrial practice, hydrocracking catalysts are mainly composed of alumina, molecular sieves, active metals and silicon-aluminum oxides, among which the carrier part (alumina, molecular sieves and silicon-aluminum oxides) plays the role of providing suitable acid sites and specific surface area to promote the chemical bond breaking and cracking of heavy oil molecules. Active metals (such as tungsten, nickel, molybdenum, etc.) are mainly responsible for hydrogenation reactions, reducing impurities such as sulfur and nitrogen in the raw materials, while improving the stability and quality of oil products.

[0004] However, existing hydrocracking catalyst technology faces some challenges, especially when processing Fischer-Tropsch wax oil. First, the current catalyst design and optimization are mainly aimed at petroleum-based feedstocks, and have limited applicability to Fischer-Tropsch synthesis products (especially Fischer-Tropsch wax oil). Secondly, conventional hydrocracking catalysts have low diesel selectivity on Fischer-Tropsch wax oil feedstocks, and the freezing point of diesel after cracking is high, which limits its application in low-temperature environments. In addition, the pore structure of the catalyst is crucial to improving the material diffusion rate and cracking efficiency, but the pore structure of conventional catalysts is often not optimized enough, resulting in limited diffusion of macromolecules in Fischer-Tropsch wax oil inside the catalyst, reducing the efficiency and selectivity of catalytic cracking.

[0005] In the prior art, there have been some attempts to improve the Fischer-Tropsch wax oil hydrocracking catalyst. For example, patent CN113908846A proposes a catalyst using modified amorphous silicon aluminum as a carrier, whose active metals are tungsten and nickel, without the need to add additional molecular sieves, and the carrier particle size is controlled within the range of 5-15 microns, in order to improve the cracking performance and economic benefits of the catalyst. Patent CN1374373A uses a specific proportion of Y zeolite, tungsten oxide or molybdenum oxide, and aluminum oxide or silicon aluminum mixture as catalyst components, aiming to improve the efficiency of the Fischer-Tropsch wax oil hydrocracking catalyst by optimizing the acid center and pore volume. CN105727981A and CN101698148A further explored ways to improve the efficiency of Fischer-Tropsch wax oil hydrocracking and oil quality by introducing layered columnar saponite and precious metals Pt and Pd, respectively.

[0006] Although the above patents have improved the performance of Fischer-Tropsch wax oil hydrocracking catalysts to a certain extent, it is often difficult to take into account the improvement of liquid recovery and economic benefits while pursuing high diesel yields. The pore structure and acid site regulation technology of the catalyst still need to be broken through to give full play to the potential of hydrocracking catalysts in the cracking process of Fischer-Tropsch wax oil. Therefore, developing efficient catalysts tailored to the characteristics of Fischer-Tropsch wax oil, optimizing its pore structure and acid site distribution, so as to improve the selectivity of diesel fractions, reduce diesel pour point, and improve diesel quality, is the focus and difficulty of current research. Summary of the invention

[0007] The main purpose of the present invention is to provide a hydrocracking catalyst and a preparation method and application thereof, so as to solve the problems in the prior art that when using Fischer-Tropsch wax oil as a raw material to prepare a diesel fraction (160-360°C), it is impossible to ensure both a high diesel yield and a high diesel fraction selectivity while taking into account the quality of the diesel; and in the prior art, the catalyst for preparing the diesel fraction using Fischer-Tropsch wax oil has the problems of complex preparation process and high preparation cost.

[0008] In order to solve the above problems, the present invention provides a method for preparing a hydrocracking catalyst, which comprises the following steps: treating amorphous silicon-alumina powder with acid and exchanging with ammonium, and then performing a first drying and a first calcination to obtain modified amorphous silicon-alumina powder; mixing the modified amorphous silicon-alumina powder, a binder and a sol agent to form, and performing a second drying and a second calcination to obtain a hydrocracking catalyst carrier; impregnating the hydrocracking catalyst carrier in an aqueous solution containing a first metal ion and a second metal ion, and then performing a third drying and a third calcination to obtain a hydrocracking catalyst; wherein the first metal ion is selected from the metal ions of Group VIB, and the second metal is selected from the metal ions of Group VIII.

[0009] Furthermore, the aqueous solution of the first metal ion and the second metal ion also includes a dispersant; preferably, the dispersant is one or more of ethylenediaminetetraacetic acid, acetic acid, acetic acid, oxalic acid, propionic acid and lactic acid; preferably, the amount of the dispersant added is 5 to 50% of the sum of the molar amounts of the first metal ion and the second metal ion.

[0010] Furthermore, the molar ratio of the first metal ion to the second metal ion is (2-6):1.

[0011] Furthermore, the weight content of silicon dioxide in the amorphous silicon aluminum powder is 30-50%, and the average pore size of the amorphous silicon aluminum powder is greater than 8nm; preferably, the weight content of silicon dioxide in the amorphous silicon aluminum powder is 35-45%, and the average pore size of the amorphous silicon aluminum powder is greater than 10nm.

[0012] Furthermore, the acid treatment process includes: mixing and stirring amorphous silicon-alumina powder with an acid solution; exchanging the amorphous silicon-alumina powder with ammonium in an aqueous solution containing ammonium, and then performing a first drying and a first calcination to obtain modified amorphous silicon-alumina powder; preferably, the acid solution has a pH of 4≤pH<7, the stirring temperature is 20-90°C, and the stirring time is 2-4h; more preferably, the acid solution has a pH of 5≤pH<7, and the stirring temperature is 30-60°C; preferably, the acid solution is one or more of an aqueous nitric acid solution, an aqueous sulfuric acid solution and an aqueous citric acid solution; preferably, the aqueous ammonium solution is an aqueous ammonium chloride solution and / or an ammonium nitrate solution; preferably, the concentration of the aqueous ammonium solution is 0.1-2mol / L.

[0013] Furthermore, in the mixing and molding process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is (60-90):(20-40):(10-40); preferably, an auxiliary agent is also added in the mixing and molding process, and the auxiliary agent is one or more of methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, sesbania powder, sesbania gum and guar gum; preferably, the auxiliary agent is methyl cellulose; preferably, the ratio of the amount of the auxiliary agent added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is (0.01-0.1):1; further preferably, the ratio of the amount of the auxiliary agent added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is (0.02-0.05):1.

[0014] Further, the binder is one or more of pseudo-boehmite, silica sol and aluminum sol; preferably, the peptization index of pseudo-boehmite is ≥90%; further preferably, the peptization index of pseudo-boehmite is ≥96%; preferably, the sol agent is one or more of nitric acid, sulfuric acid, phosphoric acid, acetic acid and citric acid; further preferably, the sol agent is nitric acid; preferably, the mass concentration of the sol agent is 0.01-10%; preferably, the mass concentration of the sol agent is 0.2-0.5%; preferably, the first metal is Mo and / or W, and the second metal is Co and / or Ni; preferably, the Mo source is an aqueous solution of ammonium molybdate, and the W source is an aqueous solution of ammonium metatungstate; preferably, the Co source is an aqueous solution of cobalt nitrate, and the nickel Ni source is an aqueous solution of nickel nitrate.

[0015] Further, the temperatures of the first drying, the second drying and the third drying are each independently selected from 100 to 300° C., and the times of the first drying, the second drying and the third drying are each independently selected from 0.5 to 24 h; and / or, the temperatures of the first roasting, the second roasting and the third roasting are each independently selected from 300 to 800° C., and the times of the first roasting, the second roasting and the third roasting are each independently selected from 0.5 to 24 h; preferably, the temperatures of the first drying, the second drying and the third drying are each independently selected from 150 to 200° C., and the times of the first drying, the second drying and the third drying are each independently selected from 2 to 6 h; and / or, the temperatures of the first roasting, the second roasting and the third roasting are each independently selected from 450 to 550° C., and the times of the first roasting, the second roasting and the third roasting are each independently selected from 2 to 6 h.

[0016] According to another aspect of the present invention, a hydrocracking catalyst is provided, which is prepared by the above-mentioned preparation method, and contains a first metal oxide and a second metal oxide; wherein the first metal oxide is selected from Group VIB metal oxides, and the second metal oxide is selected from Group VIII metal oxides; preferably, the total weight content of the first metal oxide and the second metal oxide in the hydrocracking catalyst is 5 to 35%, and the molar ratio of the first metal oxide to the second metal oxide is (2 to 6):1.

[0017] According to the third aspect of the present invention, there is also provided an application of the above hydrocracking catalyst, wherein the hydrocracking catalyst is used for hydrocracking reaction with Fischer-Tropsch wax oil as raw material; preferably, the distillation range of the Fischer-Tropsch wax oil is 250-800°C.

[0018] The present invention provides a hydrocracking catalyst and a preparation method and application thereof, the preparation method comprising the following steps: treating amorphous silicon aluminum powder with acid and ammonium exchange, and then drying and calcining it for the first time to obtain modified amorphous silicon aluminum powder; mixing and molding the modified amorphous silicon aluminum powder, a binder and a sol agent, and then drying and calcining it for the second time to obtain a hydrocracking catalyst carrier; impregnating the hydrocracking catalyst carrier in an aqueous solution containing a first metal ion and a second metal ion, and then drying and calcining it for the third time to obtain a hydrocracking catalyst; wherein the first metal ion is selected from the metal ions of the VIB group, and the second metal is selected from the metal ions of the VIII group. The present invention uses amorphous silicon aluminum powder with high pore volume and high specific surface area as the main active component of the hydrocracking catalyst carrier, and by subjecting it to acid modification and ammonium ion exchange modification, on the one hand, the pore structure and pore size distribution of the catalyst are changed, so that it has specific adsorption and diffusion properties, improves the mass transfer and diffusion effect of the macromolecular components in the Fischer-Tropsch wax oil in the catalyst, reduces the probability of secondary cracking of the product, and enables it to effectively obtain diesel fraction compounds. On the other hand, the above-mentioned modification treatment can change the acid site distribution in the hydrocracking catalyst, and can expose more effective acid sites in the catalyst carrier, so that it can be better used to control the cracking and isomerization reactions in the hydrocracking process, increase the probability of the Fischer-Tropsch wax oil contacting the active center, and make it have excellent cracking performance and improve cracking selectivity. In addition, the present invention simultaneously loads the first metal ion and the second metal ion on the hydrocracking catalyst carrier, and the synergistic effect of the two metal ions can further serve the purpose of improving the catalytic activity and stability of the hydrocracking catalyst.

[0019] In summary, the use of the above hydrocracking catalyst for preparing diesel fraction material using Fischer-Tropsch wax oil as raw material can not only improve the yield of diesel fraction material, but also improve the quality of diesel fraction material, so that the obtained diesel fraction material also has the characteristic of low freezing point. In addition, the preparation method is simple to operate and can further reduce production costs. DETAILED DESCRIPTION

[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0021] As described in the background technology section, the prior art has improved the performance of Fischer-Tropsch wax oil hydrocracking catalysts to a certain extent. However, when using Fischer-Tropsch wax oil as a raw material to prepare diesel fraction (160-360°C), especially when pursuing a high diesel yield, the hydrocracking catalysts in the prior art are often difficult to take into account the simultaneous improvement of liquid yield and economic benefits. Therefore, how to improve the selectivity of diesel fractions while lowering the diesel pour point and improving diesel quality is the focus and difficulty of current research.

[0022] In order to solve the above problems, the present invention provides a method for preparing a hydrocracking catalyst, which comprises the following steps: subjecting amorphous silicon-alumina powder to acid treatment and ammonium exchange, and then subjecting it to a first drying and a first calcination to obtain modified amorphous silicon-alumina powder; mixing the modified amorphous silicon-alumina powder, a binder and a sol agent to form, and subjecting it to a second drying and a second calcination to obtain a hydrocracking catalyst carrier; impregnating the hydrocracking catalyst carrier in an aqueous solution containing a first metal ion and a second metal ion, and then subjecting it to a third drying and a third calcination to obtain a hydrocracking catalyst; wherein the first metal ion is selected from the metal ions of Group VIB, and the second metal is selected from the metal ions of Group VIII.

[0023] In the preparation method of the hydrocracking catalyst provided by the present invention, the amorphous silicon aluminum powder is first subjected to acid treatment and ammonium exchange to improve the pore structure and the medium-strong acid content in the amorphous silicon aluminum powder, and then subjected to a first drying and a first calcination to obtain a modified amorphous silicon aluminum powder. The modified amorphous silicon aluminum powder is then mixed with a binder and a sol agent to form a good mechanical support strength through a second drying and a second calcination to obtain a hydrocracking catalyst carrier. Finally, the first metal ion and the second metal ion are loaded on the surface of the hydrocracking catalyst carrier by impregnation, and then subjected to a third drying and a third calcination to obtain a hydrocracking catalyst.

[0024] The present invention adopts amorphous silicon-alumina powder with high pore volume and high specific surface area as the main active component of the hydrocracking catalyst carrier in the present invention, and performs acid modification and ammonium exchange modification on it. On the one hand, its pore structure and pore size distribution can be optimized, the relative proportion of small pores (<5nm) can be reduced, and the relative proportion of large pores (≥5nm) can be increased, so that it has the adsorption and diffusion properties of specific reactants; on the other hand, the acid content of the catalyst can be adjusted, and its acid site distribution can be changed, so that it can better control the cracking and isomerization reactions in the hydrocracking process. The modification operation can also make the subsequent loaded active metal substances more evenly distributed, and play a better catalytic cracking role. When it is used to prepare diesel fraction materials using Fischer-Tropsch wax oil as raw material, it is beneficial to improve the distribution of diesel fractions and improve the quality of diesel fraction materials. In addition, the hydrocracking catalyst prepared by the present invention can also improve the mass transfer and diffusion effect of the macromolecular components in the Fischer-Tropsch wax oil in the catalyst, and reduce the probability of secondary cracking of the product; more acidic sites exposed in the catalyst carrier can increase the probability of the Fischer-Tropsch wax oil contacting the active center, so that it has excellent cracking performance, further improves the cracking selectivity, improves the distribution of the diesel fraction, and thus improves the yield. The first metal ion and the second metal ion are simultaneously loaded on the hydrocracking catalyst carrier, and the two metal ions act synergistically, which can further improve the catalytic activity and stability of the hydrocracking catalyst.

[0025] In summary, the hydrocracking catalyst of the present invention not only has a good pore structure, but also has good adsorption and desorption properties due to the presence of acidic sites and the first metal and the second metal, which can better control the cracking and isomerization reactions in the hydrocracking process. It is used to synthesize diesel fraction materials using Fischer-Tropsch wax oil as a raw material, and can have good specific catalytic activity and stability, which can not only improve the yield of diesel fraction materials, but also improve the quality of diesel fraction materials, so that the obtained diesel fraction materials have a lower condensation point. In addition, the preparation method of the hydrocracking catalyst is simple to operate and can further reduce production costs.

[0026] In a preferred embodiment, the aqueous solution of the first metal ion and the second metal ion further includes a dispersant; preferably, the dispersant is one or more of ethylenediaminetetraacetic acid, acetic acid, acetic acid, oxalic acid, propionic acid and lactic acid. The above-mentioned dispersants are added to the aqueous solution of the first metal ion and the second metal ion, and the added dispersant can be dissociated into R-(COO - )n, the structure can form a ligand with the first metal ion and the second metal ion. On the one hand, the formation of the ligand improves the dispersibility of the metal ions in the aqueous solution. When the hydrocracking catalyst carrier is immersed in the aqueous solution containing the first metal ion and the second metal ion, the metal ions are not easy to agglomerate on the surface of the hydrocracking catalyst carrier, and the first metal ion and the second metal ion can be more evenly distributed on the catalyst surface, further improving the catalytic activity of the hydrocracking catalyst. On the other hand, in the process of the hydrocracking catalyst carrier loading metal ions, since the first metal ion and the second metal ion in the aqueous solution are simultaneously present in the aqueous solution, the second metal ion, under the influence of its properties, will preferentially combine with the acidic site in the pore to form a chemical bond adsorption, and this feature will reduce the catalytic activity of the catalyst to a certain extent. After adding the dispersant, the bonding force between the second metal ion and the hydrocracking catalyst carrier can be reduced, and the prepared hydrocracking catalyst has a higher activity. Preferably, the amount of the dispersant added is 5 to 50% of the sum of the molar amounts of the first metal ion and the second metal ion. Controlling the amount of the dispersant added within the above range can make the above effect better.

[0027] In a preferred embodiment, the molar ratio of the first metal ion to the second metal ion is (2-6):1. The molar ratio of the first metal ion to the second metal ion in the aqueous solution of the first metal ion and the second metal ion is controlled within the above range. The obtained hydrocracking catalyst is more likely to exert its catalytic performance, and the synergistic effect between the two metals is also better, which can further improve the catalytic activity and stability of the catalyst.

[0028] In a preferred embodiment, the weight content of silicon dioxide in the amorphous silicon aluminum powder is 30-50%, and the average pore size of the amorphous silicon aluminum powder is greater than 8nm, such as 8-20nm. Modification of amorphous silicon aluminum powder with a silicon dioxide content and an average pore size of amorphous silicon aluminum powder within the above range helps to improve the acidity, pore structure and metal loading of the hydrocracking catalyst, thereby improving the specific cracking and isomerization reaction performance of the catalyst, improving the diesel selectivity and yield in the Fischer-Tropsch wax oil treatment process, and reducing the diesel pour point to meet the needs of high-quality diesel production. More preferably, the weight content of silicon dioxide in the amorphous silicon aluminum powder is 35-45%, and the average pore size of the amorphous silicon aluminum powder is greater than 10nm, such as 10-20nm. The amorphous silicon aluminum powder under the above preferred conditions is modified, and the specific catalytic effect of the prepared hydrocracking catalyst is better.

[0029] In a preferred embodiment, the acid treatment process includes: mixing and stirring amorphous silicon-alumina powder with an acid solution; exchanging the amorphous silicon-alumina powder in an aqueous solution containing ammonium, and then first drying and first calcining to obtain modified amorphous silicon-alumina powder; preferably, the acid solution has pH 4≤pH<7, the stirring temperature is 20~90℃, and the stirring time is 2~4h; more preferably, the acid solution has pH 5≤pH<7, and the stirring temperature is 30~60℃; further preferably, the acid solution is one or more of nitric acid aqueous solution, sulfuric acid aqueous solution and citric acid aqueous solution; preferably, the aqueous solution of ammonium is ammonium chloride aqueous solution and / or ammonium nitrate aqueous solution; preferably, the concentration of the aqueous solution of ammonium is 0.1~2mol / L. By adopting the above-mentioned specific treatment method and controlling the acid treatment conditions and ammonium exchange conditions within the above-mentioned range, the pore structure and medium-strong acid content of the modified amorphous silicon-alumina powder can be made more suitable, which is helpful to further improve the selectivity of the hydrocracking catalyst for diesel fractions and improve the quality of diesel. In addition, during the acid treatment process, after the amorphous silica-alumina powder is mixed and stirred with the acid solution, it is also included to wash it with water until it is neutral; after the acid-treated amorphous silica-alumina powder is subjected to ammonium exchange, it is also included to wash it to wash away the excess ammonium-containing aqueous solution on the surface to avoid the excess ammonium-containing aqueous solution affecting the catalyst performance, thereby achieving the purpose of better removing the alkali metal elements in the original powder.

[0030] In a preferred embodiment, in the mixing and forming process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is (60-90): (20-40): (10-40). Controlling the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol in the mixing and forming process within the above range can further improve the mechanical strength of the catalyst carrier, make the hydrocracking catalyst carrier have better supporting strength, and improve the activity and stability of the hydrocracking catalyst in the hydrocracking reaction. Preferably, an auxiliary agent is also added in the mixing and forming process, and the auxiliary agent is one or more of methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, sesbania powder, sesbania gum and guar gum; preferably, the auxiliary agent is methyl cellulose; preferably, the ratio of the amount of the auxiliary agent added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is (0.01-0.1): 1; further preferably, the ratio of the amount of the auxiliary agent added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is (0.02-0.05): 1. Adding an auxiliary agent during the mixing and forming process can further improve the performance of the hydrocracking catalyst carrier. By adjusting the addition ratio of the auxiliary agent in the above manner, the above effect can be further improved.

[0031] In a preferred embodiment, the binder is one or more of pseudo-boehmite, silica sol and alumina sol; preferably, the peptization index of pseudo-boehmite is ≥90%; further preferably, the peptization index of pseudo-boehmite is ≥96%; preferably, the sol is one or more of nitric acid, sulfuric acid, phosphoric acid, acetic acid and citric acid; further preferably, the sol is nitric acid; preferably, the mass concentration of the sol is 0.01-10%; preferably, the mass concentration of the sol is 0.2-0.5%. Selecting the above types of binders and sols can effectively help further improve the mechanical strength and thermal stability of the catalyst. Preferably, the first metal ion is a soluble salt of Mo and / or W, and the second metal is a soluble salt of Co and / or Ni; preferably, the Mo source is an aqueous solution of ammonium molybdate, and the W source is an aqueous solution of ammonium metatungstate; preferably, the Co source is an aqueous solution of cobalt nitrate, and the nickel Ni source is an aqueous solution of nickel nitrate. The present invention has no restrictions on the soluble metal salts corresponding to the first metal ion and the second metal ion, and the above is only an example.

[0032] In a preferred embodiment, the temperature of the first drying, the second drying and the third drying is independently selected from 100 to 300°C, and the time of the first drying, the second drying and the third drying is independently selected from 0.5 to 24 hours; and / or, the temperature of the first calcination, the second calcination and the third calcination is independently selected from 300 to 800°C, and the time of the first calcination, the second calcination and the third calcination is independently selected from 0.5 to 24 hours. Controlling the temperature and time of the first drying, the second drying and the third drying and the first calcination, the second calcination and the third calcination within the above range can further improve the performance of the hydrocracking catalyst, so that it has higher activity, selectivity and stability, as well as good mass transfer performance, thereby improving the reaction efficiency and product quality. Preferably, the temperature of the first drying, the second drying and the third drying is independently selected from 150 to 200°C, and the time of the first drying, the second drying and the third drying is independently selected from 2 to 6 hours; and / or, the temperature of the first roasting, the second roasting and the third roasting is independently selected from 450 to 550°C, and the time of the first roasting, the second roasting and the third roasting is independently selected from 2 to 6 hours. If the temperature and time of the first drying, the second drying and the third drying and the first roasting, the second roasting and the third roasting are controlled within the above preferred range, the above effect is better and the preparation efficiency can be effectively improved.

[0033] According to another aspect of the present invention, a hydrocracking catalyst is provided, which is prepared by the above preparation method, and contains a first metal oxide and a second metal oxide; wherein the first metal oxide is selected from the metal oxides of Group VIB, and the second metal oxide is selected from the metal oxides of Group VIII; preferably, the total weight content of the first metal oxide and the second metal oxide in the hydrocracking catalyst is 5-35%, and the molar ratio of the first metal oxide to the second metal oxide is (2-6): 1. By controlling the total weight content of the first metal oxide and the second metal oxide and the molar ratio of the first metal oxide to the second metal oxide in the hydrocracking catalyst to be within the above range, the hydrocracking catalyst can have better stability, selectivity and catalytic activity, and better catalytic effect.

[0034] According to the third aspect of the present invention, there is also provided an application of the above-mentioned hydrocracking catalyst, wherein the above-mentioned hydrocracking catalyst is used for a hydrocracking reaction using Fischer-Tropsch wax oil as a raw material. Preferably, the distillation range of Fischer-Tropsch wax oil is 250-800°C. Since the hydrocracking catalyst of the present invention has suitable acid sites and pore size distribution, it is used to catalyze the hydrocracking reaction using Fischer-Tropsch wax oil as a raw material, which can make it have better specific catalytic activity, especially, it can have a good effect on Fischer-Tropsch wax oil within the above-mentioned distillation range, and can prepare diesel fraction materials with high selectivity, high yield and high quality.

[0035] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0036] Example 1

[0037] Take amorphous silicon-aluminum powder (with SiO2 content of 38wt% and average pore size of 10.1nm) and place it in a nitric acid aqueous solution with a pH of 6.5, stir it at 60°C for 4h, and then wash the acid-treated amorphous silicon-aluminum powder with deionized water until it is neutral; the washed amorphous silicon-aluminum powder is ammonium exchanged in a 1mol / L ammonium chloride aqueous solution, and a solid is obtained after separation, and the separated solid is then placed at 140°C for drying for 4h, and calcined at 500°C for 4h to obtain modified amorphous silicon-aluminum powder.

[0038] Take the modified amorphous silica-alumina powder, binder (pseudo-boehmite with a peptization index of 96%), and methyl cellulose obtained above, add a sol (0.04% nitric acid aqueous solution) under stirring, mix them evenly, knead them into a shape, and then dry them at 150°C for 2h, and roast them at 500°C for 2h to obtain a hydrocracking catalyst carrier. In this process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is 75:25:20, and the ratio of the amount of the auxiliary agent methyl cellulose added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is 0.03:1.

[0039] Take the first metal ion aqueous solution (ammonium metatungstate aqueous solution) and the second metal ion aqueous solution (nickel nitrate aqueous solution) and mix them, add the dispersant ethylenediaminetetraacetic acid to mix them evenly, and make an impregnation solution, wherein the molar ratio of W ions to Ni ions in the mixed impregnation solution is 3:1, and the molar amount of ethylenediaminetetraacetic acid is 15% of the sum of the molar amounts of W ions and Ni ions. The hydrocracking catalyst carrier obtained above is impregnated in the mixed solution to load W ions and Ni ions thereon, and the carrier loaded with the first metal ions and the second metal ions is dried at 150°C for 4h, and then roasted at 500°C for 3h to prepare a hydrocracking catalyst. Among them, the weight content of the first metal oxide tungsten oxide and the second metal oxide nickel oxide is 28%, and the molar ratio of the two is 3:1.

[0040] Example 2

[0041] Take amorphous silicon-aluminum powder (with SiO2 content of 43wt% and average pore size of 10.5nm) and place it in a nitric acid aqueous solution with a pH of 6.5, stir it at 50°C for 3h, and then wash the acid-treated amorphous silicon-aluminum powder with deionized water until it is neutral; the washed amorphous silicon-aluminum powder is ammonium exchanged in a 1mol / L ammonium chloride aqueous solution, and a solid is obtained after separation, and the separated solid is then placed at 140°C for drying for 4h, and calcined at 500°C for 4h to obtain modified amorphous silicon-aluminum powder.

[0042] Take the modified amorphous silica-alumina powder, binder (pseudo-boehmite with a peptization index of 96%), and methyl cellulose, add a sol (0.04% nitric acid aqueous solution) under stirring, mix them evenly, knead them into a shape, and then dry them at 150°C for 2 hours and calcine them at 500°C for 2 hours to obtain a hydrocracking catalyst carrier. In this process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is 80:20:18, and the ratio of the amount of the auxiliary agent methyl cellulose added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is 0.03:1.

[0043] The first metal ion aqueous solution (ammonium metatungstate aqueous solution) and the second metal ion aqueous solution (nickel nitrate aqueous solution) are mixed, and the dispersant ethylenediaminetetraacetic acid is added thereto and mixed evenly to prepare an impregnation solution, wherein the molar ratio of W ions to Ni ions in the mixed solution is 3:1, and the molar amount of ethylenediaminetetraacetic acid is 25% of the sum of the molar amounts of W ions and Ni ions; the hydrocracking catalyst carrier obtained above is impregnated in the mixed solution to load W ions and Ni ions thereon, and the carrier loaded with W ions and Ni ions is dried at 150°C for 4h, and then calcined at 500°C for 3h to prepare a hydrocracking catalyst. The weight content of the first metal oxide tungsten oxide and the second metal oxide nickel oxide is 28%, and the molar ratio of the two is 3:1.

[0044] Example 3

[0045] Take amorphous silicon-aluminum powder (with SiO2 content of 38wt% and average pore size of 10.1nm) and place it in a nitric acid aqueous solution with a pH of 5.5, stir it at 50°C for 2h, and then wash the acid-treated amorphous silicon-aluminum powder with deionized water until it is neutral; the washed amorphous silicon-aluminum powder is ammonium exchanged in a 1mol / L ammonium chloride aqueous solution, and a solid is obtained after separation, and the separated solid is then placed at 140°C for drying for 4h, and calcined at 500°C for 4h to obtain modified amorphous silicon-aluminum powder.

[0046] Take the modified amorphous silica-alumina powder, binder (pseudo-boehmite with a peptization index of 96%), and methyl cellulose obtained above, add a sol (0.04% nitric acid aqueous solution) under stirring, mix them evenly, knead them into a shape, and then dry them at 150°C for 2h, and roast them at 500°C for 2h to obtain a hydrocracking catalyst carrier. In this process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is 85:15:15, and the ratio of the amount of the auxiliary agent methyl cellulose added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is 0.03:1.

[0047] The first metal ion aqueous solution (ammonium metatungstate aqueous solution) and the second metal ion aqueous solution (nickel nitrate aqueous solution) are mixed, and the dispersant ethylenediaminetetraacetic acid is added thereto and mixed evenly to prepare an impregnation solution, wherein the molar ratio of W ions to Ni ions in the mixed solution is 3:1, and the molar amount of ethylenediaminetetraacetic acid is 40% of the sum of the molar amounts of W ions and Ni ions; the hydrocracking catalyst carrier obtained above is impregnated in the mixed solution to load W ions and Ni ions thereon, and the carrier loaded with W ions and Ni ions is dried at 150°C for 4h, and then calcined at 500°C for 3h to prepare a hydrocracking catalyst. The weight content of the first metal oxide tungsten oxide and the second metal oxide nickel oxide is 28%, and the molar ratio of the two is 3:1.

[0048] Example 4

[0049] Take amorphous silicon-aluminum powder (with SiO2 content of 38wt% and average pore size of 10.1nm) and place it in a nitric acid aqueous solution with a pH of 5, stir it at 60°C for 4h, and then wash the acid-treated amorphous silicon-aluminum powder with deionized water until it is neutral; the washed amorphous silicon-aluminum powder is ammonium exchanged in a 1mol / L ammonium chloride aqueous solution, and a solid is obtained after separation, and the separated solid is then placed at 150°C for drying for 6h, and then calcined at 450°C for 6h to obtain modified amorphous silicon-aluminum powder.

[0050] Take the modified amorphous silica-alumina powder, binder (aluminum sol), and methyl cellulose obtained above, add a sol (0.5% nitric acid aqueous solution) under stirring, mix them evenly, knead them into a shape, and then dry them at 150°C for 4 hours and roast them at 500°C for 3 hours to obtain a hydrocracking catalyst carrier. In this process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is 75:25:20, and the ratio of the amount of the auxiliary agent methyl cellulose added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is 0.05:1.

[0051] Take a first metal ion aqueous solution (ammonium metatungstate aqueous solution) and a second metal ion aqueous solution (nickel nitrate aqueous solution) and mix them, add dispersant acetic acid to them and mix them evenly to make an impregnation solution, wherein the molar ratio of W ions to Ni ions in the mixed solution is 3:1, and the molar amount of acetic acid is 8% of the sum of the molar amounts of W ions and Ni ions. The hydrocracking catalyst carrier obtained above is impregnated in the mixed solution to load W ions and Ni ions thereon, and the carrier loaded with the first metal ions and the second metal ions is dried at 150°C for 4h, and then roasted at 500°C for 3h to prepare a hydrocracking catalyst. Among them, the weight content of the first metal oxide tungsten oxide and the second metal oxide nickel oxide is 28%, and the molar ratio of the two is 3:1.

[0052] Example 5

[0053] Take amorphous silicon-alumina powder (with SiO2 content of 38wt% and average pore size of 10.1nm) and place it in a nitric acid aqueous solution with a pH of 6.8, stir it at 30°C for 4h, and then wash the acid-treated amorphous silicon-alumina powder with deionized water until it is neutral; the washed amorphous silicon-alumina powder is ammonium exchanged in a 1mol / L ammonium chloride aqueous solution, and a solid is obtained after separation, and the separated solid is then dried at 200°C for 2h and calcined at 550°C for 2h to obtain modified amorphous silicon-alumina powder.

[0054] Take the modified amorphous silica-alumina powder, binder (silica sol), and methyl cellulose obtained above, add a sol (0.2% nitric acid aqueous solution) under stirring, mix them evenly, knead them into shape, and then dry them at 180°C for 3h, and calcine them at 500°C for 2h to obtain a hydrocracking catalyst carrier. In this process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is 75:25:20, and the ratio of the amount of the auxiliary agent methyl cellulose added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is 0.02:1.

[0055] Take a first metal ion aqueous solution (ammonium molybdate aqueous solution) and a second metal ion aqueous solution (cobalt nitrate aqueous solution) and mix them, add dispersant lactic acid to them and mix them evenly to make an impregnation solution, wherein the molar ratio of Mo ions to Co ions in the mixed solution is 3:1, and the molar amount of lactic acid is 45% of the sum of the molar amounts of Mo ions and Co ions. The hydrocracking catalyst carrier obtained above is impregnated in the mixed solution to load Mo ions and Co ions thereon, and the carrier loaded with the first metal ions and the second metal ions is dried at 150°C for 4h, and then calcined at 500°C for 3h to prepare a hydrocracking catalyst. Among them, the weight content of the first metal oxide molybdenum oxide and the second metal oxide cobalt oxide is 28%, and the molar ratio of the two is 3:1.

[0056] Example 6

[0057] Take amorphous silicon-alumina powder (with SiO2 content of 38wt% and average pore size of 10.1nm) and place it in a citric acid aqueous solution with a pH of 4, stir it at 90°C for 2h, and then wash the acid-treated amorphous silicon-alumina powder with deionized water until it is neutral; the washed amorphous silicon-alumina powder is ammonium exchanged in a 2mol / L ammonium nitrate aqueous solution, and a solid is obtained after separation, and the separated solid is then dried at 100°C for 24h and calcined at 800°C for 0.5h to obtain modified amorphous silicon-alumina powder.

[0058] Take the modified amorphous silica-alumina powder, binder (pseudo-boehmite with a peptization index of 90%), and sesbania powder, add a sol (0.01% sulfuric acid aqueous solution) under stirring, mix them evenly, knead them into a shape, and then dry them at 150°C for 2h, and roast them at 500°C for 2h to obtain a hydrocracking catalyst carrier. In this process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is 90:20:40, and the ratio of the amount of the auxiliary agent sesbania powder added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is 0.01:1.

[0059] Take the first metal ion aqueous solution (ammonium metatungstate aqueous solution) and the second metal ion aqueous solution (nickel nitrate aqueous solution) and mix them, add dispersant propionic acid to them and mix them evenly to make an impregnation solution, wherein the molar ratio of W ions to Ni ions in the mixed solution is 2:1, and the molar amount of propionic acid is 5% of the sum of the molar amounts of W ions and Ni ions. The hydrocracking catalyst carrier obtained above is impregnated in the mixed solution to load W ions and Ni ions thereon, and the carrier loaded with the first metal ions and the second metal ions is dried at 150°C for 4h, and then calcined at 500°C for 3h to prepare a hydrocracking catalyst. Among them, the weight content of the first metal oxide tungsten oxide and the second metal oxide nickel oxide is 5%, and the molar ratio of the two is 2:1.

[0060] Example 7

[0061] Take amorphous silicon-aluminum powder (with SiO2 content of 38wt% and average pore size of 10.1nm) and place it in a nitric acid aqueous solution with a pH of 4.5, stir it at 20°C for 4h, and then wash the acid-treated amorphous silicon-aluminum powder with deionized water until it is neutral; the washed amorphous silicon-aluminum powder is ammonium exchanged in a 0.1mol / L ammonium chloride aqueous solution to obtain a solid after separation, and then the separated solid is placed at 300°C for drying for 0.5h, and calcined at 300°C for 24h to obtain modified amorphous silicon-aluminum powder.

[0062] Take the modified amorphous silica-alumina powder, binder (pseudo-boehmite with a peptization index of 90%), and guar gum obtained above, add a sol (10% citric acid aqueous solution) under stirring, mix them evenly, knead them into a shape, and then dry them at 150° C. for 2 hours, and roast them at 500° C. for 2 hours to obtain a hydrocracking catalyst carrier. In this process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is 60:40:10, and the ratio of the amount of the auxiliary agent guar gum added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is 0.1:1.

[0063] Take the first metal ion aqueous solution (ammonium metatungstate aqueous solution) and the second metal ion aqueous solution (nickel nitrate aqueous solution) and mix them, add dispersant propionic acid to them and mix them evenly to make an impregnation solution, wherein the molar ratio of W ions to Ni ions in the mixed solution is 6:1, and the molar amount of propionic acid is 50% of the sum of the molar amounts of W ions and Ni ions. The hydrocracking catalyst carrier obtained above is impregnated in the mixed solution to load W ions and Ni ions thereon, and the carrier loaded with the first metal ions and the second metal ions is dried at 150°C for 4h, and then roasted at 500°C for 3h to prepare a hydrocracking catalyst. Among them, the weight content of the first metal oxide tungsten oxide and the second metal oxide nickel oxide is 35%, and the molar ratio of the two is 6:1.

[0064] Example 8

[0065] The difference between Example 8 and Example 1 is that, in the process of preparing the impregnation solution, no dispersant ethylenediaminetetraacetic acid is added.

[0066] Example 9

[0067] Take amorphous silicon-aluminum powder (with SiO2 content of 38wt% and average pore size of 10.1nm) and place it in a nitric acid aqueous solution with a pH of 2, stir it at 60°C for 4h, and then wash the acid-treated amorphous silicon-aluminum powder with deionized water until it is neutral; the washed amorphous silicon-aluminum powder is ammonium exchanged in a 5mol / L ammonium chloride aqueous solution, and a solid is obtained after separation, and the separated solid is then placed at 140°C for drying for 4h, and calcined at 500°C for 4h to obtain modified amorphous silicon-aluminum powder.

[0068] Take the modified amorphous silica-alumina powder, binder (pseudo-boehmite with a peptization index of 96%), and methyl cellulose, add a sol (0.04% nitric acid aqueous solution) under stirring, mix them evenly, knead them into a shape, and then dry them at 150°C for 2 hours and calcine them at 500°C for 2 hours to obtain a hydrocracking catalyst carrier. In this process, the weight ratio of the modified amorphous silica-alumina powder, the binder and the sol is 100:10:5, and the ratio of the amount of the auxiliary agent methyl cellulose added to the sum of the weight of the modified amorphous silica-alumina powder and the binder is 0.5:1.

[0069] Take the first metal ion aqueous solution (ammonium metatungstate aqueous solution) and the second metal ion aqueous solution (nickel nitrate aqueous solution) and mix them, add the dispersant ethylenediaminetetraacetic acid to mix them evenly, and make an impregnation solution, wherein the molar ratio of W ions to Ni ions in the mixed solution is 0.5:1, and the molar amount of ethylenediaminetetraacetic acid is 3% of the sum of the molar amounts of W ions and Ni ions. The hydrocracking catalyst carrier obtained above is impregnated in the mixed solution to load W ions and Ni ions thereon, and the carrier loaded with the first metal ions and the second metal ions is dried at 150°C for 4h, and then roasted at 500°C for 3h to prepare a hydrocracking catalyst. Among them, the weight content of the first metal oxide tungsten oxide and the second metal oxide nickel oxide is 3%, and the molar ratio of the two is 0.5:1.

[0070] Comparative Example 1

[0071] The difference between Comparative Example 1 and Example 1 is that the amorphous silicon-alumina powder is not modified but is directly used to prepare the hydrocracking catalyst carrier.

[0072] Comparative Example 2

[0073] The difference between Comparative Example 2 and Example 2 is that the amorphous silicon-alumina powder is not modified but is directly used to prepare the hydrocracking catalyst carrier.

[0074] Comparative Example 3

[0075] The difference between Comparative Example 3 and Example 1 is that the amorphous silicon aluminum powder is not modified and is directly used to prepare the hydrocracking catalyst carrier, and the hydrocracking catalyst carrier only loads the first metal, and the weight content of the first metal oxide tungsten oxide in the prepared hydrocracking catalyst is 28%.

[0076] The pore size distribution and medium-strong acid content of the modified amorphous silicon-aluminum powder used to prepare the hydrocracking catalyst carrier in Examples 1 to 9 and the amorphous silicon-aluminum powder used to prepare the hydrocracking catalyst carrier in Comparative Examples 1 to 3 were tested, and the results are shown in Table 1. Among them, the amorphous silicon-aluminum powder used to prepare the hydrocracking catalyst carrier in Comparative Examples 1 and 2 is the amorphous silicon-aluminum powder before modification in Examples 1 to 9.

[0077] About the test method of pore size distribution and the test method of medium and strong acid content:

[0078] Pore ​​size distribution test method: The pore structure of amorphous silicon aluminum powder samples was determined using an ASAP2420 surface analyzer. The chemical pulse adsorption method was used to determine and record the desorption area of ​​the sample after nitrogen adsorption at liquid nitrogen temperature. The sample was pretreated at 350°C for 8 hours before the measurement. The pore size distribution of the sample was calculated using the BJH model.

[0079] Test method for medium-strong acid content: The determination of the medium-strong acid content of amorphous silicon aluminum powder samples was carried out on a Quantachrome ChemBET Pulsar programmed temperature chemical adsorption instrument. The carrier gas was high-purity helium with a flow rate of 120 mL / min and a catalyst loading of 0.2 g. The catalyst was activated from room temperature to 550°C at a rate of 10°C / min, maintained for 1 hour, cooled to 80°C to adsorb ammonia to saturation, purged for 30 minutes to remove physically adsorbed NH3, and then heated to 550°C at a rate of 10°C / min, and the desorption curve was recorded.

[0080] Table 1-1

[0081]

[0082] Table 1-2

[0083]

[0084] The pore size distribution of the hydrocracking catalysts prepared in the above examples and comparative examples was tested for relevant performances, and the results are shown in Table 2.

[0085] Table 2

[0086]

[0087]

[0088] The hydrocracking catalysts prepared in the above embodiments and comparative examples are used to prepare diesel using Fischer-Tropsch wax oil as raw material, wherein the information of the Fischer-Tropsch wax oil used is shown in Table 3. When the conversion rate of each catalyst is controlled to be 60% during use, the diesel selectivity and the pour point of the prepared diesel are tested, and the results are shown in Table 4. The test methods involved are as follows: pour point: according to the national standard GB / T510-2018 method, the HP850C instrument of Heilchao Company of Germany is used for determination; diesel selectivity calculation method: the conversion rate of the hydrocracking reaction and the selectivity of diesel (160-360°C fraction) are calculated using the data of simulated distillation, wherein the proportion of diesel (160-360°C fraction) in the chromatogram is X1, and the proportion of unconverted components (360-FBP) is X2; liquid yield Y1 = C3 in the product + Mass / incoming feed weight×100%, feed conversion rate TC=(1-X2*Y1)×100%, diesel (160-360℃ fraction) selectivity S1=(X1*Y1) / TC×100%.

[0089] Table 3

[0090] project Refined tail oil 20℃ density / (g / cm3) 0.79 Condensation point / ℃ 105 Distillation range (D2887) / ℃ 360~650 0.5% / 5% 355 / 390 10% / 30% 402 / 440 50% / 70% 480 / 521 90% / 95% 579 / 600 99.5% 650

[0091] Table 4

[0092] Conversion rate, wt% Diesel selectivity, wt% Diesel condensation point, ℃ Example 1 60 74 -19 Example 2 60 72 -21 Example 3 60 77 -20 Example 4 60 73 -22 Example 5 60 71 -19 Example 6 60 69 -20 Example 7 60 70 -17 Example 8 60 67 -18 Example 9 60 65 -14 Comparative Example 1 60 62 -13 Comparative Example 2 60 63 -12 Comparative Example 3 60 57 -11

[0093] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0094] Examples 1 to 9 are methods for modifying amorphous silicon-aluminum powders for preparing hydrocracking catalysts using the method for modifying amorphous silicon-aluminum powders of the present invention. As can be seen from the data in Table 1-1, the pore structure of the modified amorphous silicon-aluminum powders has undergone significant changes, with the relative proportion of small pores (<5nm) significantly reduced and the relative proportion of large pores (≥5nm) significantly increased. In addition, the content of medium-strong acid in the modified amorphous silicon-aluminum powders can also be significantly increased relative to the unmodified amorphous silicon-aluminum powders, which is beneficial for the hydrocracking catalysts prepared subsequently to have more acidic sites, further improving the catalytic effect of the catalysts. In particular, in Examples 1 to 8, the modification effect of the amorphous silicon-aluminum powders is more obvious. The pore size distribution and medium-strong acid content of the unmodified amorphous silicon-aluminum powder in Comparative Examples 1 to 3 are shown in Tables 1-2. From the data in the table, it can be seen that the proportion of small pores (<5nm) in the amorphous silicon-aluminum powder before modification is relatively high, the relative proportion of large pores (≥5nm) is relatively low, and the medium-strong acid content is also lower.

[0095] The pore size distribution of the hydrocracking catalyst prepared in the embodiment and the comparative example was tested, and the results are shown in Table 2. As can be seen from the data in Table 2, when preparing the hydrocracking catalyst in the present invention, the amorphous silicon aluminum powder used is first modified, which can effectively improve the pore size distribution of the hydrocracking catalyst, and the pore size ratio of <5nm is significantly reduced, the pore size ratio of ≥5nm is significantly increased, and the average pore size is also significantly increased. The above pore size distribution ratio can enable it to have specific adsorption and diffusion properties. However, the hydrocracking catalyst prepared in the comparative example has a higher pore size ratio of <5nm and a smaller average pore size, which is not conducive to adsorption and diffusion in the hydrocracking process.

[0096] The hydrocracking catalyst prepared by the present invention is used for hydrocracking reaction with Fischer-Tropsch wax oil as raw material, wherein the information of Fischer-Tropsch wax oil is shown in Table 3. It can be seen from the results in Table 4 that when the conversion rate of the raw material Fischer-Tropsch wax oil in the preparation process is controlled to be 60%, the selectivity of Examples 1 to 9 for the diesel fraction is all above 65%, and the prepared diesel has good quality. In particular, in Examples 1 to 7, the selectivity for the diesel fraction is better, the quality of the prepared diesel is also better, and the selectivity of the catalyst for the diesel fraction can even reach 77%. The hydrocracking catalysts prepared by Comparative Examples 1 and 2 have lower selectivity for the diesel fraction and worse quality. In Comparative Example 3, the hydrocracking catalyst prepared not only does not modify the amorphous silicon-aluminum powder, but also contains only the first metal in the catalyst. Therefore, the catalyst prepared by using it has lower selectivity for the diesel fraction, and the quality is also far from that in the embodiments of the present invention.

[0097] In summary, the present invention adopts amorphous silicon-alumina powder with high pore volume and high specific surface area as the main active component of the hydrocracking catalyst carrier, and optimizes its pore structure by acid modification and ammonium exchange treatment, reduces the relative proportion of small pores (≤5nm), and increases the relative proportion of large pores (>5nm); the medium-strong acid content of the amorphous silicon-alumina used to prepare the catalyst is also improved. When the hydrocracking catalyst is used to prepare diesel fraction materials using Fischer-Tropsch wax oil as a raw material, it can better control the cracking and isomerization reactions in the hydrocracking process, which is beneficial to improve the distribution of diesel fractions and improve the quality of diesel fraction materials. It can also improve the mass transfer and diffusion effect of the macromolecular components in Fischer-Tropsch wax oil in the catalyst and reduce the probability of secondary cracking of the product. More effective acid sites exposed in the catalyst can increase the probability of Fischer-Tropsch wax oil contacting the active center, so that it has excellent cracking performance, improves cracking selectivity, improves the distribution of diesel fractions, and thus improves the yield. The first metal ion and the second metal ion are simultaneously loaded on the hydrocracking catalyst carrier, and the two metal ions act synergistically to further improve the catalytic activity and stability of the hydrocracking catalyst.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrocracking catalyst, characterized in that: The preparation method comprises the following steps: The amorphous silicon-aluminum powder is subjected to acid treatment and ammonium exchange, and then subjected to a first drying and a first calcination to obtain a modified amorphous silicon-aluminum powder; The modified amorphous silicon-alumina powder, a binder and a sol are mixed and molded, and subjected to a second drying and a second calcination to obtain a hydrocracking catalyst carrier; The hydrocracking catalyst carrier is immersed in an aqueous solution containing a first metal ion and a second metal ion, and then subjected to a third drying and a third calcination to obtain the hydrocracking catalyst; wherein the first metal ion is selected from Group VIB metal ions, and the second metal is selected from Group VIII metal ions.

2. The method for preparing a hydrocracking catalyst according to claim 1, characterized in that: The aqueous solution of the first metal ion and the second metal ion further includes a dispersant; Preferably, the dispersant is one or more of ethylenediaminetetraacetic acid, acetic acid, acetic acid, oxalic acid, propionic acid and lactic acid; Preferably, the added amount of the dispersant is 5-50% of the sum of the molar amounts of the first metal ion and the second metal ion.

3. The method for preparing the hydrocracking catalyst according to claim 1 or 2, characterized in that: The molar ratio of the first metal ion to the second metal ion is (2-6):

1.

4. The method for preparing a hydrocracking catalyst according to any one of claims 1 to 3, characterized in that: The weight content of silicon dioxide in the amorphous silicon aluminum powder is 30-50%, and the average pore size of the amorphous silicon aluminum powder is greater than 8nm; Preferably, the weight content of silicon dioxide in the amorphous silicon-aluminum powder is 35-45%, and the average pore size of the amorphous silicon-aluminum powder is greater than 10 nm.

5. The method for preparing a hydrocracking catalyst according to any one of claims 1 to 3, characterized in that: The acid treatment process comprises: mixing and stirring the amorphous silicon aluminum powder with an acid solution; The modified amorphous silicon-aluminum powder is obtained by subjecting the amorphous silicon-aluminum powder to the ammonium exchange in an aqueous solution containing ammonium, and then subjecting the amorphous silicon-aluminum powder to the first drying and the first calcination; Preferably, the acid solution has a pH of 4≤pH<7, the stirring temperature is 20-90°C, and the stirring time is 2-4h; More preferably, the acid solution has a pH of 5≤pH<7, and the stirring temperature is 30-60°C; Preferably, the acid solution is one or more of an aqueous nitric acid solution, an aqueous sulfuric acid solution and an aqueous citric acid solution; Preferably, the aqueous ammonium solution is an aqueous ammonium chloride solution and / or an aqueous ammonium nitrate solution; Preferably, the concentration of the aqueous ammonium solution is 0.1-2 mol / L.

6. The method for preparing a hydrocracking catalyst according to any one of claims 1 to 3, characterized in that: In the mixed molding process, the weight ratio of the modified amorphous silicon aluminum powder, the binder and the sol agent is (60-90): (20~40):(10~40); Preferably, an auxiliary agent is further added during the mixing and forming process, and the auxiliary agent is one or more of methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, sesbania powder, sesbania gum and guar gum; Preferably, the auxiliary agent is methyl cellulose; Preferably, the ratio of the amount of the additive added to the sum of the weight of the modified amorphous silicon aluminum powder and the binder is (0.01-0.1):1; Further preferably, the ratio of the amount of the additive added to the sum of the weight of the modified amorphous silicon aluminum powder and the adhesive is (0.02-0.05):

1.

7. The method for preparing a hydrocracking catalyst according to any one of claims 1 to 3, characterized in that: The binder is one or more of pseudo-boehmite, silica sol and alumina sol; Preferably, the peptization index of the pseudo-boehmite is ≥90%; Further preferably, the peptization index of the pseudo-boehmite is ≥96%; Preferably, the sol agent is one or more of nitric acid, sulfuric acid, phosphoric acid, acetic acid and citric acid; further preferably, the sol agent is nitric acid; Preferably, the mass concentration of the sol agent is 0.01 to 10%; Preferably, the mass concentration of the sol agent is 0.2-0.5%; Preferably, the first metal is Mo and / or W, and the second metal is Co and / or Ni; Preferably, the Mo source is an aqueous solution of ammonium molybdate, and the W source is an aqueous solution of ammonium metatungstate; Preferably, the Co source is an aqueous solution of cobalt nitrate, and the Ni source is an aqueous solution of nickel nitrate.

8. The method for preparing a hydrocracking catalyst according to any one of claims 1 to 7, characterized in that: The temperatures of the first drying, the second drying and the third drying are independently selected from 100 to 300° C., and the times of the first drying, the second drying and the third drying are independently selected from 0.5 to 24 hours; and / or, The temperatures of the first calcination, the second calcination and the third calcination are independently selected from 300 to 800° C., and the times of the first calcination, the second calcination and the third calcination are independently selected from 0.5 to 24 hours; Preferably, the temperatures of the first drying, the second drying and the third drying are each independently selected from 150 to 200° C., and the times of the first drying, the second drying and the third drying are each independently selected from 2 to 6 hours; and / or, The temperatures of the first calcination, the second calcination and the third calcination are independently selected from 450 to 550° C., and the times of the first calcination, the second calcination and the third calcination are independently selected from 2 to 6 hours.

9. A hydrocracking catalyst, characterized in that The hydrocracking catalyst is prepared by the preparation method according to any one of claims 1 to 8, and the hydrocracking catalyst contains a first metal oxide and a second metal oxide; wherein the first metal oxide is selected from Group VIB metal oxides, and the second metal oxide is selected from Group VIII metal oxides; Preferably, the total weight content of the first metal oxide and the second metal oxide in the hydrocracking catalyst is 5-35%, and the molar ratio of the first metal oxide to the second metal oxide is (2-6):

1.

10. Use of the hydrocracking catalyst according to claim 9, characterized in that: The hydrocracking catalyst is used to carry out a hydrocracking reaction using Fischer-Tropsch wax oil as a raw material; Preferably, the distillation range of the Fischer-Tropsch wax oil is 250-800°C.

Citation Information

Patent Citations

  • Noble metal catalyst used in hydrocracking and isomerization of Fischer-Tropsch synthetic wax and preparation method therof

    CN101698148A

  • Fischer-Tropsh synthetic wax hydrocracking catalyst, preparation method and application thereof

    CN105727981A

  • Hydrocracking catalyst as well as preparation method and application thereof

    CN113908846A

  • Catalyst for producing diesel oil from Fischer-Tropsch synthetic wax and its prepn and use

    CN1374373A